Organizing U.S. foreign aid : confronting the challenges of the twenty-first century - Lancaster, Carol (Global economy and development., 2005)
"Recommends fundamental reorganization of U.S. foreign aid, currently based on outsourcing and management for results, in favor of a more unified approach emphasizing development education, stringent evaluation, and a new approach to contracting"--Provided by publisher